Ziziphora Capitata L. Ethanolic Extract: Evaluation Of Antioxidant Properties, Enzyme Inhibition, Genotoxic And Antigenotoxic Activities (Bangladesh Journal of Botany, 2026)
Ziziphora capitata L. is used in traditional medicine. The objective of this study was to assess the antioxidant capacity, total phenolic content, elastase, collagenase, and hyaluronidase inhibition, as well as the genotoxic and antigenotoxic properties of the ethanol extract obtained from the aerial parts of Z. capitata. The antioxidant activity was evaluated using DPPH and β-carotene bleaching assays, which revealed moderate radical scavenging effects with IC50 values of 200 ± 1.13 µg/ml and 138 ± 2.37 µg/ml, respectively. The total phenolic content was determined to be 36 ± 3.7 mg of gallic acid equivalent per gram of extract, thereby substantiating its antioxidative potential. The extract selectively inhibited collagenase (16.51 ± 0.5%) and hyaluronidase (5.94 ± 0.17%). The extract was determined to be non-genotoxic, and it exhibited a reduction in genotoxicity induced by NaN3 and 4-NPD. Collectively, these findings suggest that Z. capitata may represent a promising natural source with potential applications in wound healing.Bangladesh J. Bot. 55(1): 167-172, 2026 (March)